CD317-Positive Immune Stromal Cells in Human “Mesenchymal Stem Cell” Populations - Kay, Alasdair G.; Fox, James M.; Hewitson, James P.; Stone, Andrew P.; Robertson, Sophie; James, Sally; Wang, Xiao-nong; Kapasa, Elizabeth; Yang, Xuebin B.; Genever, Paul G. (Frontiers in Immunology, 2022)
Heterogeneity of bone marrow mesenchymal stromal cells (MSCs, frequently referred to as “mesenchymal stem cells”) clouds biological understanding and hampers their clinical development. In MSC cultures most commonly used in research and therapy, we have identified an MSC subtype characterised by CD317 expression (CD317pos (29.77±3.00% of the total MSC population), comprising CD317dim (28.10±4.60%) and CD317bright (1.67±0.58%) MSCs) and a constitutive interferon signature linked to human disease. We demonstrate that CD317pos MSCs induced cutaneous tissue damage when applied a skin explant model of inflammation, whereas CD317neg MSCs had no effect. Only CD317neg MSCs were able to suppress proliferative cycles of activated human T cells in vitro, whilst CD317pos MSCs increased polarisation towards pro-inflammatory Th1 cells and CD317neg cell lines did not. Using an in vivo peritonitis model, we found that CD317neg and CD317pos MSCs suppressed leukocyte recruitment but only CD317neg MSCs suppressed macrophage numbers. Using MSC-loaded scaffolds implanted subcutaneously in immunocompromised mice we were able to observe tissue generation and blood vessel formation with CD317neg MSC lines, but not CD317pos MSC lines. Our evidence is consistent with the identification of an immune stromal cell, which is likely to contribute to specific physiological and pathological functions and influence clinical outcome of therapeutic MSCs.